TIME-SLOTTED LORA MAC WITH VARIABLE PAYLOAD SUPPORT - Triantafyllou, Anna; Zorbas, Dimitrios; Sarigiannidis, Panagiotis (Computer Communications, 2022)
LoRaWAN is an upcoming Low Power Wide Area Network (LPWAN) technology for Internet of Things implementations in various application domains. Despite its various advantages, LoRaWAN employs an Alohabased MAC, which in terms of performance cannot guarantee high packet delivery ratio and low latency. To overcome this issue, we propose a time-slotted scheme, called TS-VP-LoRa, which supports multiple transmission times and packet sizes at the same time. In TS-VP-LoRa, scheduling is coordinated by the LoRa gateway, broadcasting beacon frames periodically for the synchronization of LoRa end-devices. A channel hopping mechanism is also proposed in order to minimize the occurrence of collisions and to evenly split the transmission load among all channels. TS-VP-LoRa is evaluated and compared to three other MAC-layer schemes in single gateway simulation scenarios with up to 500 nodes. The proposed scheme has proven to achieve low latency with high packet delivery ratios, significantly minimize collisions and maintain a relatively low energy consumption despite the scaling of the LoRa network.
Keywords: Type of access: Open Access; LoRa; LoRaWAN; Aloha; Time-slotted; Synchronization